A Novel Guidewire Pull-Through Technique in Endovascular Treatment for Severely Calcified Infrapopliteal Occlusion - Ueno, Daisuke (Am J Case Rep, 2020)
Patient: Female, 74-year-old Final Diagnosis: Arteriosclerosis obliterans Symptoms: Skin ulcers Medication: — Clinical Procedure: — Specialty: Cardiology OBJECTIVE: Unusual or unexpected effect of treatment BACKGROUND: In practical settings of endovascular treatment (EVT) for below-the-knee arteries, we often encounter cases of severe calcification. To overcome problems regarding device uncrossing due to severe calcifications, a bidirectional approach and subsequent guidewire externalization is one of critical methods. CASE REPORT: A 74-year-old female with refractory skin ulcers on the lower frontal thigh and necrotic toes on the left side showed occlusion in both the anterior tibial artery (ATA) and tibio-peroneal trunk. Both occluded vessels were accompanied with dense calcification. In the process of EVT targeting the occluded ATA, the retrograde guide-wire successfully passed the occlusion and was advanced into the antegrade guide sheath. Next, we attempted guidewire externalization, but severe calcification of the ATA hampered the procedure. Therefore, we introduced a guide extension catheter and a balloon catheter in an antegrade fashion to establish a system of trapping the retrograde guidewire between these devices. Then, we pulled the system back outside the guide sheath, which completed guidewire externalization. We performed prolonged balloon dilatation and finally achieved favorable revascularization of the ATA. CONCLUSIONS: Our novel method led to successful retrograde guidewire externalization, overcoming severely calcified lesions. It is generally essential for clinicians to increase their expertise regarding EVT procedures to attain better outcomes.